Cross-sectional survey for assessing cancer care providers' characteristics and attitudes on smoking cessation in Colombia and Mexico. Issue 2 (1st February 2021) - Tami-Maury, Irene; Suchil, Laura; Reynales-Shigematsu, Luz Myriam; Garcia-Gomez, Leonor; Chen, Mixing; Shete, Sanjay; Betancur, Alejandro; Cinciripini, Paul M; Hawk, Ernest; Garcia, Hector
Abstract : Objective: Cancer care providers' (CCPs) attitudes towards smoking cessation are influenced by many factors, including their smoking status and knowledge. Our objective was to assess CCPs' characteristics, tobacco use and smoking cessation practices in two Latin American cancer centres. Design: Cross-sectional survey. Settings: Two urban cancer centres located in Colombia and Mexico. Participants: A total of 238 CCPs. Measures: Online survey consisted of 28 close-ended questions adapted from the 2012 International Association for the Study of Lung Cancer survey and the Global Adult Tobacco Survey developed by the WHO. Means, frequencies and proportions were reported for each country. Factors associated to providing of smoking cessation treatment or referral at initial visit were evaluated using logistic regression. Results: Current smoking prevalence was 10.5% and 12.3% among Colombian and Mexican CCPs, respectively. Around three quarters of the Colombian (86.4%) and Mexican CCPs (66.1%) considered to have inadequate training in smoking cessation. Approximately two-thirds of Colombian (67.5%) and Mexican CCPs (63.9%) reported always or most of the time asking patients about tobacco use during the initial visit. In Colombia and Mexico, the most relevant barriers for providing cessation services were (1) difficulties for motivating patients with cancer, (2) patient resistance in quitting smoking, (3) lack of local resources or referral centres for smoking cessation and (4) lack of training in smoking cessation. CCPs appointed at Instituto Nacional de Cancerología were less likely to provide cessation treatment or referral to their patients if they had less than 50% of their time devoted to patient care and were former or current smokers. The regression model for Instituto de Cancerología did not retain statistically significant variables. Conclusion: Our findings highlight an urgent need for assisting Latin American CCPs in their quitting efforts as well as expanding formal smoking cessation training specifically tailored to these professionals for improving patients' cancer prognosis and quality of life.